Whole-rock elemental and zircon Hf isotopic geochemistry of mafic and ultramafic rocks from the Early Cretaceous Comei large igneous province in SE Tibet: constraints on mantle source characteristics and petrogenesis - Zhu, Di-Cheng; Mo, Xuan-Xue; Zhao, Zhi-Dan; Niu, Yaoling; Chung, Sun-Lin (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1350 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.178-180